What is the distance in space between the points with coordinates (-3,6,7) and (2,-1,4) ?

Answers

Answer 1
Answer: A(-3;\ 6;\ 7);\ B(2;-1;\ 4)\n\n|AB|=√((2-(-3))^2+(-1-6)^2+(4-7)^2)\n\n=√(5^2+(-7)^2+(-3)^2)=√(25+49+9)=√(83)

Related Questions

A hardcover book sells for 24$ at the bookmart. Ben pays 25.02 for the book. What is the sales tax rate?
P(A) = 0.44 What are the odds for A?
A university interested in tracking its honors program believes that the proportion of graduates with a GPA of 3.00 or below is less than 0.20. In a sample of 200 graduates, 30 students have a GPA of 3.00 or below.
Complete the square t^2+10t=75
A color printer prints 28 pages in 8 minutes.How many pages does it print per minute?

Two landscapers must mow a rectangular lawn that measures 100 feet by 200 feet. Each wants to mow no more than half of the lawn. The first starts by mowing around the outside of the lawn. How wide a strip must the first landscaper mow on each of the four sides in order to mow no more than half of the lawn? The mower has a 24-inch cut. Approximate the required number of trips around the lawn.

Answers


The total area of the complete lawn is (100-ft x 200-ft) = 20,000 ft².
One half of the lawn is  10,000 ft².  That's the limit that the first man
must be careful not to exceed, lest he blindly mow a couple of blades
more than his partner does, and become the laughing stock of the whole
company when the word gets around.  10,000 ft² ... no mas !

When you think about it ... massage it and roll it around in your
mind's eye, and then soon give up and make yourself a sketch ...
you realize that if he starts along the length of the field, then with
a 2-ft cut, the lengths of the strips he cuts will line up like this:

First lap:
       (200 - 0) = 200
       (100 - 2) = 98
       (200 - 2) = 198
       (100 - 4) = 96    

Second lap:
       (200 - 4) = 196
       (100 - 6) = 94
       (200 - 6) = 194
       (100 - 8) = 92   

Third lap:
       (200 - 8) = 192
       (100 - 10) = 90
       (200 - 10) = 190
       (100 - 12) = 88 

These are the lengths of each strip.  They're 2-ft wide, so the area
of each one is (2 x the length). 

I expected to be able to see a pattern developing, but my brain cells
are too fatigued and I don't see it.  So I'll just keep going for another
lap, then add up all the areas and see how close he is:

Fourth lap:
       (200 - 12) = 188
       (100 - 14) = 86
       (200 - 14) = 186
       (100 - 16) = 84 

So far, after four laps around the yard, the 16 lengths add up to
2,272-ft, for a total area of 4,544-ft².  If I kept this up, I'd need to do
at least four more laps ... probably more, because they're getting smaller
all the time, so each lap contributes less area than the last one did.

Hey ! Maybe that's the key to the approximate pattern !

Each lap around the yard mows a 2-ft strip along the length ... twice ...
and a 2-ft strip along the width ... twice.  (Approximately.)  So the area
that gets mowed around each lap is (2-ft) x (the perimeter of the rectangle),
(approximately), and then the NEXT lap is a rectangle with 4-ft less length
and 4-ft less width.

So now we have rectangles measuring

         (200 x 100),  (196 x 96),  (192 x 92),  (188 x 88),  (184 x 84) ... etc.

and the areas of their rectangular strips are
           1200-ft², 1168-ft², 1136-ft², 1104-ft², 1072-ft² ... etc.

==> I see that the areas are decreasing by 32-ft² each lap.
       So the next few laps are 
               1040-ft², 1008-ft², 976-ft², 944-ft², 912-ft² ... etc. 

How much area do we have now:

             After 9 laps,    Area =   9,648-ft²
             After 10 laps,  Area = 10,560-ft².

And there you are ... Somewhere during the 10th lap, he'll need to
stop and call the company surveyor, to come out, measure up, walk
in front of the mower, and put down a yellow chalk-line exactly where
the total becomes 10,000-ft².   


There must still be an easier way to do it.  For now, however, I'll leave it
there, and go with my answer of:  During the 10th lap.

How do you do,
csc2x-cot2x = tanx

Answers

csc2x-cot2x=tanx \n  \n   ((1)/(2)cscxsecx) -( (cotx-tanx)/(2) )=tanx \n  \n  ((cscxsecx)/(2)) -( (cotx-tanx)/(2) )=tanx  \n  \n  (( (1)/(sinx)  (1)/(cosx) )/(2)) -( (cotx-tanx)/(2) )=tanx \n  \n   ((1)/(2(sinxcosx))) -( (cotx-tanx)/(2) )=tanx \n  \n ((1)/(2(sinxcosx))) -( ((sinxcosx)*cotx-tanx)/(2*(sinxcosx)) )=tanx  \n  \n  (1-(cos^2x-sin^2x))/(2(sinxcosx)) =tanx \n \n (1-cos^2+sin^2x)/(2(sinxcosx))=tanx

(sin^2x+sin^2x)/(2(sinxcosx)) =tanx \n  \n  (1-cos2x)/(sin2x) =tanx \n  \n  (sin2x)/(cos2x+1)=tanx \n  \n tanx=tanx


What is the first term of the geometric sequence presented in the table below? n 4 9 an 243 59,049

Answers

Reminder:  the formula for a geom. seq. is

a(n) = a(1)*r^(n-1), where a(1) is the first term, n is the counter and r is the common ratio. 

I first noted that 243 is a power of 3; specifically, 243=3^5, or 243=3(3)^4, or 243=(3^2)(3)^(4-1).  Notice that I'm trying here to rewrite 243=3^5 in the form a(n) = a(1)*r^(n-1):    a(4) = a(1)(3)^(4-1), or a(4) = a(1)(3)^3 = 243.  Then by division we find that a(1) = 243/27 = 9.  Is it possible that a(1)=9?

Let's try out our formula   a(n)=9(3)^(n-1).  Steal n=9 and see whether this formula gives u s 59049:

n(9) = 59049 = 9(3)^(9-1), or  9(3)^8.  True or false?  3^8= 6561, and 9(3)^8 = 59049.

YES!  That's correct.

Therefore, the desired formula is

a(n) = 9(3)^(n-1).  The first term, a(1) is 9(3)^(1-1) = 9(3)^0 = 9*1 = 9.

Final answer:

The first term of the geometric sequence is 3. Calculation is done using the formula for the nth term of a geometric sequence and substituting the given values.

Explanation:

To find the first term of the geometric sequence, one can use the formula for the nth term of a geometric sequence, which is a = arn-1. Here, 'a' is the first term, 'r' is the common ratio and 'n' is the term position. As provided in the table, when n=4, an=243 and when n=9, an=59049. We can setup the equation 243 = a*r3 and 59049 = a*r8. Dividing the second equation by the first we get r5 = 243, leading to r=3. Substitute r=3 into the first equation to find 'a' and we get a= 3.

Learn more about geometric sequence here:

brainly.com/question/33243139

#SPJ3

A and B share money in a ratio of 9:4. How much of the £39000 does B get?

Answers

so we have a total of 39000
and a total of 9+4 parts to split it in
so split 39000 into 13 parts
39000/13 = 3000
9:4
9(3000) : 4(3000)
27000:12000
I was going to answer your question but someone did it

What is 4-6h-8h=60 abnswer

Answers

4 - 6h - 8h = 60

First, simplify. / Your problem should look like: 4 - 14h = 60
Second, subtract 4 from both sides. / Your problem should look like: -14h = 60 - 4
Third, subtract 60 - 4. / Your problem should look like: -14h = 56
Fourth, divide both sides by -14. / Your problem should look like: h =  (56)/(-14)
Fifth, simplify the fraction into a negative. / Your problem should look like: h =  -(56)/(14)
Sixth, since 4 goes into 14 to get 56, simplify the fraction by 4. / Your problem should look like: h = -4

Answer: h = -4

Sally earns graduated commission on her sales each month. She earns 6% commission on the first $45,000 in sales and 8% on anything over that. If Sally had $51,000 in sales this month, how much commission did she earn?

Answers

Sally earns commission depending on her sales per month.She said to be earning 6% for the first 45 000 dollars in her sales.Now, she will be receiveing another 8% on anything that is over the said sales.Given that Sally were able to reach 51 000 dollars sales.Let's find how much is her total commission:=> 45 000 dollars * .06 = 2700 dollars=> 51 000 dollars - 45 000 dollars = 6 000 dollars=> 6 000 dollars * .06 = 360 dollars=> 2 700 dollars + 360 = 3060 dollars.

Answer:

The answer is B. $3,180. I tried the $3,060 as someone stated above, and it was wrong on Edgen.

Step-by-step explanation: